PUBLIC GOVERNANCE CAPACITY IN THE ACCOUNTABILITY OF VILLAGE-OWNED ENTERPRISE MANAGEMENT IN INDONESIA - Denok Kurniasih; Paulus Israwan Setyoko (Lembaga Penelitian Universitas Pasundan, 2019)
The Indonesian Government has encouraged the development of village-owned business as an alternative utilization of village transfer fund. The trust of the Indonesian government in the village government has been seen from the transfer of funds given to the village. This fund aims to develop their village. Building village-owned business should certainly be counterbalanced with a public accountability mechanism. This research aims at describing the capacity of public governance in the accountability system performed by public sector organization. This research also explores public capacity in supporting the accountability of BUMDes management from a cultural perspective. Village communities have distinct characteristics where not all systems can operate without local wisdom. This research employs both quantitative and qualitative approaches and use questionnaire and interview guide as its instruments. This research is conducted in Banyumas and takes 41 village business units and informants consisting of village business manager, village official and villager elements as the samples. The data and information are analyzed using quantitative descriptive analysis method with support of information analyzed using interactive analysis method. The research results show that public governance capacity in the accountability of village business management is still low. The opportunity of stakeholders’s involvement in public accountability system is not yet created by public organization. This is due to the strong patrenalistic culture among Indonesian society. The village community tends to give full trust and to the village government, especially the village head. This kind of patrenalistic culture opens opportunities for not optimal accountability horizontally. Consequently, the accountability only applies vertically. This research suggests improving the capacity of public governance in the accountability system of village-owned business management through optimizing stakeholders’ role in the accountability of Village-Owned Enterprise’s management. Keywords: Accountability, local wisdom, public governance capacity, stakeholders, Village-Owned Enterprise.